2020
DOI: 10.1007/978-3-030-59722-1_75
|View full text |Cite
|
Sign up to set email alerts
|

BEFD: Boundary Enhancement and Feature Denoising for Vessel Segmentation

Abstract: Blood vessel segmentation is crucial for many diagnostic and research applications. In recent years, CNN-based models have leaded to breakthroughs in the task of segmentation, however, such methods usually lose high-frequency information like object boundaries and subtle structures, which are vital to vessel segmentation. To tackle this issue, we propose Boundary Enhancement and Feature Denoising (BEFD) module to facilitate the network ability of extracting boundary information in semantic segmentation, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 29 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The dilated convolution, which expands the receptive area without parameters increasing, is widely adopted in vessel segmentation [39]. Additionally, to prevent the attenuation of the edge information of blood vessels, researchers employed a combination of unsupervised edge detection and deep networks [41]. Therefore, combining the dilated convolution and edge detection method is an effective method to capture the local characterizations of neighboring pixels while expanding the local receptive field of the network.…”
Section: B Dual Local Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dilated convolution, which expands the receptive area without parameters increasing, is widely adopted in vessel segmentation [39]. Additionally, to prevent the attenuation of the edge information of blood vessels, researchers employed a combination of unsupervised edge detection and deep networks [41]. Therefore, combining the dilated convolution and edge detection method is an effective method to capture the local characterizations of neighboring pixels while expanding the local receptive field of the network.…”
Section: B Dual Local Attentionmentioning
confidence: 99%
“…To adjust the receptive field more flexibly without increasing computational cost, the dilated convolution was applied to replace the original convolution for medical images segmentation tasks [40]. To address the edge attenuation in segmentation results, Zhang et al also studied a boundary enhancement method with Sobel operators, alleviating the loss of vessel edge [41]. In addition, recent studies showed that the deep features and shallow features in a deep neural network can be complementary [42].…”
Section: Introductionmentioning
confidence: 99%
“…The shallower high-resolution layer is used to solve the problem of pixel positioning, and the deeper layer is used to solve the problem of pixel classification [5]. However, the U-Net still has some disadvantages and shortcomings, such as:effective convolution increases the difficulty, universality of model design, and the form of trimming is not symmetrical with the Feature Map [6].…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, hand-crafted filters [12,13,16,27] like Gabor [13] and Gaussian-based ones [12] are explored to extract features for pixel selection, vessel clustering and segmentation. Recently, data-driven based methods utilize UNet-based model [17] or its variants [24,25,28,29,10] to achieve significant performance compared with traditional methods. Those deep learning methods focus on the design of UNet structures with better feature representation [28,24], or the decouple of structure and textures of retinal images [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, data-driven based methods utilize UNet-based model [17] or its variants [24,25,28,29,10] to achieve significant performance compared with traditional methods. Those deep learning methods focus on the design of UNet structures with better feature representation [28,24], or the decouple of structure and textures of retinal images [29]. However, datadriven methods highly suffer from over-fitting issues when the given training data is insufficient.…”
Section: Introductionmentioning
confidence: 99%